The Agriculture Industry in Trinidad and Tobago: Perspectives of Industry Professionals - M’Randa R. Sandlin (Journal of International Agricultural and Extension Education, 2015)
Agricultural technology dissemination is critical to establishing food security. These technologies support proper, environmentally responsible food production and can empower producers. The purpose of this study was to describe the current condition of the farming industry in Trinidad and Tobago from the perspective of agricultural professionals. There were 22 participants who represented farmers’ market employees, farmers using conventional growing methods, farmers using innovative growing methods, and farmer training professionals. Participants were interviewed. Three themes emerged from the data: crop production methods, sources of information, and perceived needs to improve the industry. Findings revealed the need for a more centralized dissemination of information and training materials, governmental support and public awareness of agriculture efforts, and career potential. It can be concluded that environmentally responsible production methods are being diffused and some chose to reject such innovations due to the relative advantage of the farming techniques they are currently using. It can also be concluded farmers prefer informal information sources and, as a result, these are a primary change agent in the agriculture industry. Implications exist for the creation and delivery of education and training efforts for extension providers and producers.
Keywords: managing change; technology transfer; case study research; training and development; change theory